Value investment strategies inspired by ‘’The Dogs of the Dow’’ : Empirical evidence from the Helsinki Stock Exchange 2004-2023 - Sipilä, Johanna (My University, 2025)
The main purpose of this study is to determine whether dividend yield investment strategies are effective in the Finnish stock market. In addition, extending the DoD10-strategy approach in two value portfolios enables a framework to evaluate whether a value exposure generates abnormal returns. Two additional portfolios will be constructed, inspired by the DoD, using P/E-ratio and ROE as stock picking criteria. The sample will cover the years from 2004 to 2023 of every stock listed on the Helsinki Stock Exchange. This thesis aims to analyze the performance on a raw and risk-adjusted basis, using the standard portfolio performance measurement presented by Sharpe (1966) and Treynor (1965). In this study, the results of the t-statistic testing for raw returns, OMXHCAP, market-adjusted, and CAPM-adjusted returns will be presented. The results indicate that these three strategies are beating the benchmark index in terms of raw and risk-adjusted returns. The DoD-10 portfolio provides the highest risk-adjusted return in terms of systematic and total risk. In addition, all of the investment strategies tested generate abnormal returns, taking into account risk-adjustments, transaction costs, and taxes. Moreover, the results suggest convincing evidence of the outperformance against the reference index of Value investment strategies inspired by ‘’The Dogs of the Dow’’
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance